Wine tourism - a proposal for the development of the Trás-os-Montes wine route - Correia, Ricardo (2019)
The goal of this research focuses on the proposal to develop the Trás-os-Montes wine route on the premise that the failure to do so is failing to take advantage of a regional asset that should be enhanced and trumpeted, in keeping with the ancient and singular traditions of the surrounding territory. It is considered that the effective value of this research is centered on the modelling of an achievable and entrepreneurial concept, which merges with the particularities of a low-density territory, whose success will have to go through the creation of wealth in the region and full restructuring of Trás-os-Montes, as a mediator and integrator project of the whole region, in a configuration of the brand "Trás-os-Montes". It was adopted a qualitative approach, which begins with a literature review and is founded on the analysis of a case study, complemented with a documentary analysis. Six semi-structured interviews were elaborated, which substantiate the results presented. The main limitations of this study are its academic nature, which limits the exploration of this subject by its theoretical nature and presents a simplistic view, whose number of respondents could be broader, and the dense extension of the territory made impossible a "surgical" analysis, especially with regard to the identification of existing wine tourism resources.